Internalization of Pluralism Value in Adolescents Social Behavior (Case Study in Kapencar Village, Kertek, Wonosobo) - Chintia, Maya; Masrukhi, Masrukhi; Sunarjan, Y Y F R (JESS (Journal of Educational Social Studies), 2018)
Degeneration of pluralism value in some regions occurs due to the difference of religion. The plurality of religion in Kapencar, Kertek, Wonosobo, does not bring degradation of pluralism value. The aims of the research were to analyze (1) the social behavior practice of adolescents pluralism value (2) the role of family, school, and society in internalization of adolescent social behavior. The research used qualitative method with case study approach. The research was conducted periodically for 5 months. The subject was the adolescents, families, schools, and society. The data collection techniques were participatory observation, structure and in-depth interview, and documentation. The validity test of the data used triangulation of data source, technique, and time. The data analysis technique and interpretation were narrowing the focus, reviewing the data, connecting the finding, sumarizing, testing the finding, assessing the literature, making analytical analogy. The results of the research were (1) the social behavior practice of adolescents pluralism value were prioritizing tolerance, respecting, trusting, and appreciating to the plurality. (2) the role of the family through habitus was giving guidance to the adolescents to choose religion, giving advice to associate democratically, inheriting pluralism value, gathering routinely in spare time. School also internalized habitus such as giving the student time to worship in school, forcing respect and appreciate the teachers, visiting friends, helding open school of feast religios day. Moreover, the role of society in internalization of adolescent pluralism value was done by forming the member of interfaith village government, helding live in event for the adolescents, helding village merti, art, sport tournament, and celebration of big day), interfaith meeting, and helding open house religious day. All the habitus were internalized for the adolescent gradually through life habit over a long time.